PENERAPAN KONSEP BALANCED SCORECARD DALAM MANAJEMEN PERPAJAKAN (STUDI KASUS PADA WAJIB PAJAK BADAN DI KOTA SURAKARTA) - UNIBA Surakarta, Trimurti (Manajemen Bisnis Syariah, 2011)
This research have a purpose to appraise company position include implement control function in a taxation management in one of Agency Tax Obligation in Surakarta City. Tax Controlling with perform obligation review taxation as totally means phenomenological concept Balanced Scorecard which measure subservience level, law and order operational level and administration. As a whole, analysis result show that in executing entire taxation obligation of company performanced told “orderly” with the value review 73,40 or reached 95,32% from maximum value equal 77. With maximum value review for aspect of lease compliance tax, operational orderliness and administration tax equal 25, 12 and 40, so level attainment of company performance for the third aspect equal to 76%, 91,67% and 52,50%. Among the third aspect, the law and order in tax administration need more legal treatment to gain more saving in the field of tax management program. Key word : Tax Review, Balance Scorecard Concept, Tax Management.